Relationship Between Hydrocarbon Composition on the Cuticle of Melipona quadrifasciata (Hymenoptera: Apidae) Workers and the Secretion of the Cephalic Salivary Glands - Poiani, S. B. [UNESP]; Morgan, E. D.; Drijfhout, F. P.; Cruz-Landim, C. [UNESP] (Univ Estadual Feira Santana, 2018)
Since chemical communication is pivotal for social insect success, the present paper aimed to quantify and qualify the chemical compounds that might have pheromonal role in both cephalic salivary gland and epicuticle of workers of Melipona quadrifasciata Lepeletier using gas chromatographymass spectrometry (GC/MS). The results indicated that the hydrocarbons were the main compounds in both cephalic salivary gland and epicuticle, followed by esters. Positive Mantel correspondence analysis suggests that the glands could contribute to replenishment of surface compounds as an auxiliary source. Discriminant analysis also pointed out that gland and epicuticle chemical profiles were phase-related.
Keywords: CHC; labial gland; Mantel; pheromone; stingless bee